THE LEARNING OUTCOME IN THEORY AND PRACTICE OF TEACHING THE UKRAINIAN LANGUAGE FOR PROFESSIONAL PURPOSES - Humeniuk, Iryna (Mountain School of Ukrainian Carpaty, 2020)
The article examines the theoretical and practical aspects of learning outcomes formulation taking into account the global educational tendencies. The aim of the article is formation of theoretical understanding of the end result of studying the «Ukrainian Language for Professional Purposes» course at pedagogical institutions of higher education. For achievement of the goal, a set of smaller tasks have been outlined: determination of the functional load of preliminary formulation of learning outcomes; clarification of indicators of skillfully formulated learning results; comparative analysis of programmatic results of studying the «Ukrainian Language for Professional Purposes» discipline in educational programmes of selected institutions of higher education and assessment of their conformity to the aims of the educational programme of the course. A set of methods has been used in the research process: theoretical – the method of reflexive and comparative analysis (to clarify the essence of the concept «learning outcomes»); the methods of visualisation and generalisation (to determine the indicators of clearly formulated learning results and to construct matrices); the methods of mathematical and statistical processing (to form the understanding of the potential of the «Ukrainian Language for Professional Purposes» course, which has been shown in the programmatic outcomes of learning). On the basis of structural differences between the educational aims and learning results, the necessity of clear formulation of the latter has been emphasized and their functional load has been determined. The indicators of clearly formulated learning outcomes have been defined: student orientation; conformity with the aims of the educational programme; concentration on products of learning; clearness of formulation; quantitative conformity with the content and resources of the discipline; realism; suitability for measurement and assessment. Quantitative and qualitative analyses of programmatic outcomes of learning in educational programmes of selected pedagogical institutions of higher education have been performed. As a result, certain inaccuracies in their formation and necessity of specification of the evaluated learning outcomes at the level of each discipline have been detected.